A Convenient Thermal Performance Evaluating Method for Unitary AC (DX) Units. (2015) - Zheng, Keke; Cho, Young K.
Abstract: For most light commercial buildings and residential houses, the thermal energy system is usually a unitary air system and only rated as standard-satisfied during the initial installation and commission phase, regardless of the performance during the whole life cycle. Further, the thermal energy system is normally equipped with low initial cost and simple controller, usually one thermostat, which results in the poor maintenance since no specific diagnostic sensors were installed. The maintenance is required only when the system capacity is degraded and no longer satisfied, which already results in large amount of energy wasting. Existing evaluation methods for building thermal energy system have two major limitations. Firstly, they mainly work for those with advanced building automation system (BAS) control, which is extremely costly and usually adopted for large commercial building. Secondly, advanced specific knowledge is required, which is relatively complicated for average residents. This study developed a convenient method for the thermal performance evaluation of these DX or Unitary AC units: provide one simple and convenient method to quantify the thermal performance and continuously monitor thermal performance during the whole life-cycle period; present a building thermal performance rating procedure; implement the proposed method through either field data or standard compliant as-built simulation.